2002
DOI: 10.1002/chin.200218030
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Synthesis, X‐Ray and Neutron Diffraction Characterization and Ionic Conduction Properties of a New Oxothiomolybdate Li3 [Mo8S8O8(OH)8{HWO5 (H2O)}]×18H2O.

Abstract: Synthesis, X-Ray and Neutron Diffraction Characterization and Ionic Conduction Properties of a New Oxothiomolybdate Li-Title compound (IV) crystallizes in the monoclinic space group C2/m with Z = 2 (single crystal XRD). The structure contains pillars of Li + ions and ring-shaped anions formed by four hydroxo-bridged [Mo 2 S 2 O 2 ] building blocks which encapsulate a central W V I O 6 octahedron. Pressed pellets of (IV) exhibit a good room temperature conductivity (σ = 10 −5 S/cm), while the ionic conductivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
1
0
0
Order By: Relevance
“…It was observed that the samples are highly resistive (sheet resistance ∼18 GΩ/sq). The result is within the expected range as reported in an earlier study by Dolbecq et al, where they also found such high resistance of the polytungstate material.…”
Section: I–v Characteristicssupporting
confidence: 92%
“…It was observed that the samples are highly resistive (sheet resistance ∼18 GΩ/sq). The result is within the expected range as reported in an earlier study by Dolbecq et al, where they also found such high resistance of the polytungstate material.…”
Section: I–v Characteristicssupporting
confidence: 92%